Appraisal of Main Extreme Parameters of Earthquakes in Nigeria Using the Weibull Equations - A. A. Abong; B. U. Asuquo; C. A. Ushie (Archives of Current Research International, 2020)
This study investigated earthquake occurrences in Nigeria using the Weibull equations. The data employed in this study was the historical and instrumental data recorded from 1933 to 2018. The relationship between intensity scale and Richter magnitude scale given by Gutenberg and Richter was used to convert from intensity scale to Richter scale. The Weibull equations were used to compute probabilities and return periods of earthquakes. The findings of the study revealed that the return period for an earthquake of magnitude 6.5 on Richter’s scale is 86 years; an earthquake of magnitude 4.7 is 34.4 years; an earthquake of magnitude 4.2 is 17.2 years and earthquake of magnitudes 2-3.7 is between 5.56-14.3years. This implies that Nigeria may not likely experience any earthquake of magnitude 6.5 till the year 2025 since earthquake of magnitude 6.5 last occurred in 1939 but the probability of occurrence is 1.16% or 0.0116. Earthquakes of highest magnitudes 6.5, 4.7 and 4.2 on Richter’s scale for a 100 year period which indicate the most hazardous in the location with probabilities exceedance of 1.16%, 2.91% and 4.65% were evaluated. It was observed that as the time increases the probability of occurrence of these earthquakes increases with it and vice versa with magnitude 4.2 having (99.1%), magnitude 4.7 having (94.8%) and magnitude 6.5 having (80.07%). But earthquake forecast or prediction is still a complicated issue due to saturation of earthquake magnitudes and variation in seismic data collection by different seismic stations and networks. The implication of this study is that the findings will help Nigeria government to protect its people, infrastructures and the constructions that are going to take place especially earthquake – prone areas like southwestern Nigeria.